2012
DOI: 10.47102/annals-acadmedsg.v41n7p281
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Features in Enteric Fever

Abstract: Introduction: Enteric fever is a common infection in endemic areas; however, there are few reports describing the computed tomography (CT) manifestations of enteric fever. We aim to describe and illustrate CT findings in enteric fever in this study. Materials and Methods: A retrospective search of medical records in our institute for patients with positive blood cultures for Salmonella typhi, and Salmonella paratyphi organisms yielded 39 cases. Among these patients, 12 had undergone a CT study of the abdomen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As per the present case bleeding per rectum in the presence of enteric fever was also documented in a review of 552 patients of culture-proven typhoid fever in Bangladesh, which showed that rectal bleeding was seen in 9% of cases across all the age groups 6. In another study, the CT scan findings of patients with enteric fever those who had a longer clinical course, with less specific symptoms favouring the diagnosis of enteric and those having complications like rectal bleeding were found to have mesenteric lymphadenopathy and splenomegaly (75%), circumferential small bowel wall thickening (58.3%) and ascites (50%) 7. The authors also explained that these radiological features may overlap with other abdominal infections.…”
Section: Discussionmentioning
confidence: 97%
“…As per the present case bleeding per rectum in the presence of enteric fever was also documented in a review of 552 patients of culture-proven typhoid fever in Bangladesh, which showed that rectal bleeding was seen in 9% of cases across all the age groups 6. In another study, the CT scan findings of patients with enteric fever those who had a longer clinical course, with less specific symptoms favouring the diagnosis of enteric and those having complications like rectal bleeding were found to have mesenteric lymphadenopathy and splenomegaly (75%), circumferential small bowel wall thickening (58.3%) and ascites (50%) 7. The authors also explained that these radiological features may overlap with other abdominal infections.…”
Section: Discussionmentioning
confidence: 97%
“…Computed tomography shows terminal ileal circumferential thickening, lymphadenopathy, and free fluid in the abdomen which are seen in 50–75% of patients. 4 Thus, the symptomatology and imaging features of enteric fever often resemble tuberculosis and create a dilemma. We recently came across three such cases of enteric fever which mimicked tuberculosis on imaging.…”
Section: Introductionmentioning
confidence: 99%